PENGARUH PEMBERIAN PUPUK KANDANG TERHADAP HASIL KEDELAI (Glycine max L) PADA COCOPEAT - Oktabriana, Giska (Faculty of Agriculture, Universitas Malikussaleh, 2018)
The purpose of this research is to investigate the impact of application of manure on soybean yield on cocopeat and in order to get the appropriate dose for the soybean crop. Research was done using Completely Randomized Design (CRD) which consists of 4 treatments and 3 replications. There are 12 unit of experiments with composition: A = control (without fertilizer), B = cocopeat + 100 g manure / polybag and C = cocopeat + 200 g manure / polybag, cocopeat + 300 g manure / polybag. The research revealed that the application of manure can increase the soybean yield on cocopeat